2015
DOI: 10.1099/jmm.0.000008
|View full text |Cite
|
Sign up to set email alerts
|

Modified 16S–23S rRNA intergenic region restriction endonuclease analysis for species identification of Enterococcus strains isolated from pigs, compared with identification using classical methods and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry

Abstract: Fast and reliable identification of bacteria to at least the species level is currently the basis for correct diagnosis and appropriate treatment of infections. This is particularly important in the case of bacteria of the genus Enterococcus, whose resistance profile is often correlated with their species (e.g. resistance to vancomycin). In this study, we evaluated restriction endonuclease analysis of the 16S-23S rRNA gene intergenic transcribed spacer (ITS) region for species identification of Enterococcus. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…The gradual development of the proteomic technique MALDI-TOF MS has provided new opportunities for precise microbiological analysis. Numerous studies have shown that MALDI-TOF MS is a rapid, reliable, and cost-effective technique for identification of different groups of microorganisms [ 20 , 58 – 61 ], including Enterococcus [ 25 , 62 , 63 ]. In our study, we also obtained high log (score) values (> 2) for all the strains tested and the results were consistent with those of molecular identification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gradual development of the proteomic technique MALDI-TOF MS has provided new opportunities for precise microbiological analysis. Numerous studies have shown that MALDI-TOF MS is a rapid, reliable, and cost-effective technique for identification of different groups of microorganisms [ 20 , 58 – 61 ], including Enterococcus [ 25 , 62 , 63 ]. In our study, we also obtained high log (score) values (> 2) for all the strains tested and the results were consistent with those of molecular identification.…”
Section: Discussionmentioning
confidence: 99%
“…Identification to the genus Enterococcus was performed as previously described [ 12 ]. Species identification was performed using 16S–23S rRNA intergenic region restriction endonuclease analysis according to previously described protocols [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…In this study, there was a slight discrepancy between biochemical and PCR results for species identification, which is in accordance with other studies. 20 21 The main reason for this discrepancy is the similarities between Enterococcus species and the high phenotypic variation within individual species. PCR is a more accurate technique in comparison to the biochemical approach, so PCR results were preferred for the strains with discrepant identification.…”
Section: Discussionmentioning
confidence: 99%
“…A relatively new identification method using a MALDI-TOF MS system with prior formic acid extraction has provided excellent diagnostic results and reduced identification time (Seng et al, 2009;Wieser et al, 2012). MALDI-TOF MS is a rapid and accurate technique for the identification of various types of Grampositive or Gram-negative bacteria (Kosikowska et al, 2014;Marek et al, 2015;Nowakiewicz et al, 2015).…”
mentioning
confidence: 99%